In vitro activity of imipenem/releactam and comparator agents against clinical bacterial isolates from patients with cancer. (June 2022) - Rolston, Kenneth V.I.; Gerges, Bahgat Z.; Reitzel, Ruth; Shelburne, Samuel A.; Aitken, Samuel L.; Raad, Issam I.; Prince, Randall A.
Highlights: Imipenem/Relebactam is active against 98% of Enterobacteriales from cancer patients Imipenem/Relebactam had potent activity against ESBL producing E. coli and K. pneumoniae Potent activity against achromobacter spp . And non-MDR p. aeruginosa Inhibited 87% of non-enterobacterales isolates excluding s. maltophilia Moderate activity against MDR p. aeruginosa ABSTRACT: Objectives: Gram-negative bacilli (GNB) are currently the predominant bacterial pathogens in patients with cancer. Many GNB have become problematic due to the widespread emergence of resistance. Imipenem/relebactam (IMI/REL) is a combination of the carbapenem imipenem with relebactam, a non–β-lactam β-lactamase inhibitor. It is active against most pathogenic GNB including many that are resistant to other agents. We compared its in vitro activity to six other agents against 490 GNB recovered exclusively from patients with cancer because such data are scarce. Methods: Clinical and Laboratory Standards Institute (CLSI) microbroth dilution methods were used for susceptibility testing. Whole genome sequencing (Illumina MiSeq) was performed on 30 selected isolates. Results: IMI/REL was active against 98% of Enterobacterales and 87% of non- Enterobacterales isolates (excluding Stenotrophomonas maltophilia ). It had potent activity against extended spectrum β-lactamase-producing Escherichia coli, Klebsiella pneumoniae, and other Enterobacterales ( Enterobacter cloacae, Citrobacter Spp., and Serratia Spp.) and moderate activity against carbapenem-resistant Enterobacterales. IMI/REL had potent activity against Achromobacter Spp., non–multidrug resistant Pseudomonas aeruginosa, and Sphingomonas paucimobilis and moderate activity against multidrug resistant P. aeruginosa . Overall, IMI/REL was associated with the lowest number of nonsusceptible isolates compared with six other agents (imipenem, meropenem, cefepime, piperacillin/tazobactam, amikacin, and tigecycline) commonly used in patients with cancer. Whole genome sequencing performed on 30 resistant isolates (10 each of E. coli, K. pneumonia, and P. aeruginosa ) did not reveal any predominant mechanism of resistance to IMI/REL. Conclusion: Its in vitro activity indicates that IMI/REL might have a role to play in the treatment of Gram-negative infections in patients with cancer.